A microscopic investigation of ion and electron transport in lithium-ion battery porous electrodes using the lattice Boltzmann method. (15th May 2017) - Jiang, Z.Y.; Qu, Z.G.; Zhou, L.; Tao, W.Q.
Highlights: Lattice Boltzmann method is utilized to predict the ion and electron transport. The lithium concentration and electric potential distribution were obtained. The particle size and electrode porosity affect the discharge process. The electrode microstructure affects the battery performance. Abstract: Improving the cycle life and reliability of a battery is an important issue in lithium-ion battery (LIB) applications. Except for the material properties of the battery electrodes, the morphological features of LIBs also have a great influence on battery performance. In order to identify the relation between the morphological features of the electrodes and the macroscopic battery performance, a two-dimensional (2D) lattice Boltzmann model of ion and electron transport within LIB porous electrodes is presented in this study. The proposed model is superior to previous finite element method (FEM)-based models by providing a more convenient geometry generation process and a more efficient calculation technique. In the simulation, the lattice Boltzmann method (LBM) is utilized to solve the governing equations for ion and electron transport. The quartet structure generation set (QSGS) is employed to generate the electrode geometry with circular particles. The effects of the electrode micro-structure on the local concentration distribution, electric potential, and macroscopic discharge performance are investigated. Results show that the LBM is an optional approach in solving problems related to mass transport and electrochemical reactions. For the electrode particles, the obvious variations in local lithium concentration and electric potential prove that the electrode microstructure can influence the microscopic lithium transport; specifically, the lithium exchange is improved for smaller particle sizes. As for discharge performance, larger discharge depth can be achieved by a smaller cathode particle size and a larger cathode porosity. Meanwhile, a larger anode particle size and a smaller anode porosity both contribute to a larger discharge depth.